Triglyceride-glucose index as a mediator of body mass index and cardiovascular disease in middle-aged and older Chinese adults: a nationally representative longitudinal cohort study - Gan, Ying-Yuan; Zhai, Lu; Liao, Qian; Huo, Rong-Rui (Frontiers in Endocrinology, 2024)
BackgroundBody mass index (BMI) consistently correlates with the triglyceride-glucose (TyG) index, a marker of insulin resistance, which in turn is linked to heightened cardiovascular disease (CVD) risk. Thus, insulin resistance could potentially mediate the association between BMI and CVD risk. However, few studies have explored this mechanism in the general population.MethodsWe used data from the China Health and Retirement Longitudinal Study, which is an ongoing prospective cohort study. It initially enrolled 7233 middle-aged and older Chinese adults who were free of heart disease and stroke at baseline. The exposure variable was BMI. Incident CVD, defined as self-reported physician-diagnosed heart disease and stroke combined, served as the main outcome.ResultsOf the 7 233 participants (mean [SD] age, 58.93 [9.33] years), 3 415 (47.2%) were men. During the 7 years of follow-up, 1 411 incident CVD cases were identified. Both BMI and TyG index were associated with CVD risk (HR per 1-SD increase: BMI, 1.23; 95% CI, 1.17–1.29; TyG, 1.13; 95% CI, 1.07–1.19). The 4-way decomposition analysis show that, overweight increased CVD risk by 28% (HR [total association], 1.28; 95% CI, 1.14–1.45), with 18.1% (95% CI, 2.2%–34.0%) mediated by TyG index (HR [pure indirect association], 1.05; 95% CI, 1.02–1.09); while obesity increased CVD risk by 91% (HR [total association], 1.91; 95% CI, 1.63–2.23), with 9.5% (95% CI, 2.2%–16.7%) mediated by TyG index (HR [pure indirect association], 1.09; 95% CI, 1.03–1.15). No evidence suggested TyG index modified BMI’s association with incident CVD.ConclusionsThe study revealed that the TyG index was associated to CVD risk and acted as a small partial mediator in the relationship between BMI and CVD among middle-aged and older Chinese adults. Consequently, solely addressing insulin resistance might not significantly mitigate the impact of body weight on CVD. Thus, exploring alternative pathways and potential mediators of CVD risk becomes imperative.